Sociodemographic and Clinical Predictors of the Length of Psychiatric Inpatient Stay of Immigrants in Switzerland - Frizi, Renée; Lay, Barbara; Seifritz, Erich; Kawohl, Wolfram; Habermeyer, Benedikt; Roser, Patrik (Frontiers in Psychiatry, 2020)
Immigrants with mental disorders have consistently been reported to spend shorter time in the psychiatric hospital compared to native patients. The aim of this study was to identify sociodemographic, clinical and migration-related predictors of a shorter length of psychiatric inpatient stay among immigrants in Switzerland. All patients of a foreign nationality admitted for inpatient treatment in the year 2016 (N = 279) were included in this study. The sample characteristics were drawn from the register of the psychiatric hospital. Within this sample, self-harm and substance use predicted a shorter inpatient treatment episode whereas disturbances of general psychosocial functioning were a predictor of a longer length of stay. As similar results were also reported for non-immigrant patients, the impact of these specific behavioral and social problems on the length of inpatient stay does not appear to be migrant-specific. Moreover, a country of origin outside Europe was a strong predictor of shorter length of stay pointing to inequalities of inpatient psychiatric treatment within the group of immigrants. Therefore, the cultural background and migrant history of immigrants in psychiatry need stronger consideration in order to eliminate disadvantages in mental health care.